Labor and Training - Marcio Pochmann (Universidade Federal do Rio Grande do Sul, 2012)
The emergence of new forms of work, associated with the increase in the populations' life expectancy, connects with the perspective of changes in educational training. Among other characteristics, education ceases tocenter solely in the early phases of life to be lifelong. In this transformation, the understandin gamong social actors is a necessary condition to a better efficient allocation of means of production. By the same token, the possibility presents of sharing new gains of productivity with a higher threshold of civility than that of the twentieth century. Sustainable forms of production and of work organization require a basis of professional education and training.